Vape-Demic: Pengaruh Lingkungan Pergaulan terhadap Penularan Penggunaan Vape (Rokok Elektrik) menggunakan Model SEIR - Prily Azizah Humu; Indah Chairun Nisa; Aprilia Pangemanan Montolalu Jehosua; Syeren Kowaas; Nopsi Kilaaku (Griya Journal of Mathematics Education and Application, 2026)
The use of vape among teenagers and young adults has increased in recent years and is influenced by social environments. This study aimed to analyze the influence of social interaction on the spread of vape use using the Susceptible, Exposed, Infected, Recovered (SEIR) model. This research used a quantitative approach with an epidemiological mathematical modeling method. Data were collected through an online survey using Google Forms involving young people in Tondano from March 12, 2026 to May 10, 2026. The study sample consisted of 54 respondents selected using purposive sampling techniques. Data analysis was conducted by calculating the SEIR model parameters based on survey results, followed by simulation using RStudio to observe the dynamics of population changes in each group. The results showed that social interaction had a significant influence on the spread of vape use. The β parameter value of 0.444 indicated the influence of social interaction on susceptible individuals. The α parameter value of 0.923 showed that individuals who became interested in vape had a high probability of becoming active users, while the γ parameter value of 0.541 indicated that some active users were able to stop using vape. Simulation results demonstrated that the number of active vape users increased over time due to social environmental influences. This study shows that the SEIR model can be applied to analyze the spread of social behavior, particularly vape use behavior.